Medical Thoracoscopic Thermal Ablation Therapy for Metastatic Pleural Tumors with Malignant Effusion: An Exploratory Retrospective Study - Mai Z (Dove Medical Press, 2021)
Zhonglun Mai,1,* Bin Feng,2,* Qianwen He,3 Qixiao Feng1 1Department of Thoracic Oncology, Cancer Center, Integrated Hospital of Traditional Chinese Medicine, Southern Medical University, Guangzhou, Guangdong Province, 510315, People’s Republic of China; 2Department of Oncology, The First Affiliated Hospital of Jinan University, Guangzhou, Guangdong Province, 510630, People’s Republic of China; 3Department of Geriatrics, Integrated Hospital of Traditional Chinese Medicine, Southern Medical University, Guangzhou, Guangdong Province, 510315, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qixiao Feng Tel +86 18520088212Email cxhfqx@163.comZhonglun Mai Email maizhonglun@126.comPurpose: Malignant pleural effusion (MPE) is an intractable condition. The current mainstream therapies for MPE, ie, indwelling pleural catheter and pleurodesis, have some drawbacks. In this retrospective study, we explored the efficacy and safety of medical thoracoscopic thermal ablation (argon plasma coagulation, APC) therapy for metastatic pleural tumors with MPE.Patients and Methods: A total of 176 patients were enrolled and divided into catheter pleural drainage (CPD) group (n = 77), non-ablation group (n = 46), and thermal ablation group (n = 53). Propensity score matching (PSM) was used for between-group comparisons to minimize bias. The primary endpoints were pleural effusion objective response rate (ORR) and time to progression (TTP); secondary endpoints included overall survival (OS), chest-tube duration, and safety.Results: Thermal ablation group and non-ablation group showed significantly higher ORR and shorter chest-tube duration versus the CPD group (ORR: thermal ablation, 88.2% vs 66.7%, P = 0.004; non-ablation, 88.4% vs 64.4%, P = 0.042; chest-tube duration: thermal ablation, 4.90 vs 7.24 days, P < 0.001; non-ablation, 5.73 vs 7.33 days, P = 0.010). Thermal ablation group exhibited longer TTP than the CPD group (median, 13.7 vs 7.3 months, P = 0.001) and the non-ablation group (median, 13.6 vs 10.3 months, P = 0.037). OS in the thermal ablation group was numerically longer than that in the CPD group with marginally significant difference (P = 0.055). There was no significant difference in the frequency of adverse events or changes in vital signs between thermal ablation and non-ablation groups.Conclusion: Medical thoracoscopic thermal ablation (APC technique) therapy was effective and safe in the treatment of metastatic pleural tumors with MPE for improving ORR and TTP.Keywords: medical thoracoscopy, thermal ablation, argon plasma coagulation, metastatic pleural tumor, malignant pleural effusion, non-small-cell lung cancer